42.8k views
14 votes
–10 times the first equation and 3 times the second equation

10 times the first equation and 3 times the second equation
–3 times the first equation and 5 times the second equation
3 times the first equation and 5 times the second equation

–10 times the first equation and 3 times the second equation 10 times the first equation-example-1
User Bmkrio
by
5.9k points

2 Answers

10 votes

Answer:

Its the second one x=5

Explanation:

I took the test.

User Magnetron
by
5.9k points
8 votes

Answer:

-10 times the first equation and 3 times the second equation

Explanation:

Multiply the first equation by 10 and the second equation by -3:

1. 1/5 x + 3/4 y = 9

x-10 ⇒ -2x - 15/2 y = -90

2. 2/3 x - 5/6 y = 8

x3 ⇒ 2x - 5/2 y = 24

Add the equations together:

-2x - 15/2 y = -90

+ 2x - 5/2 y = 24

-------------------------

0x - 10y = -66

User Chris
by
5.3k points